Cardiovascular disease and diabetes in HIV‐positive and HIV‐negative gay and bisexual men over the age of 55 years in Australia: insights from the Australian Positive & Peers Longevity Evaluation Study. Issue 2 (26th November 2018) - Puhr, R; Petoumenos, K; Huang, R; Templeton, DJ; Woolley, I; Bloch, M; Russell, D; Law, MG; Cooper, DA
Abstract : Objectives: As HIV‐positive people age, diagnosis and management of comorbidities associated with ageing are of increasing concern. In this study, we aimed to compare the self‐reported prevalences of heart disease, stroke, thrombosis and diabetes in older Australian HIV‐positive and HIV‐negative gay and bisexual men (GBM). Methods: We analysed data from the Australian Positive & Peers Longevity Evaluation Study (APPLES), a study of a prospectively recruited cross‐sectional sample of 228 (51.1%) HIV‐positive and 218 (48.9%) HIV‐negative GBM, aged ≥ 55 years. Regression methods were used to assess the association of HIV status with self‐reported comorbidities. Results: Of 446 patients, 389 [200 (51.4%) HIV‐positive] reported their disease history. The reported prevalence of comorbidities was higher in the HIV‐positive group than in the HIV‐negative group: heart disease, 19.5 versus 12.2%; stroke, 7.5 versus 4.2%; thrombosis, 10.5 versus 4.2%; and diabetes, 15.0 versus 9.0%, respectively. In adjusted analyses, HIV‐positive GBM had significantly increased odds of reporting heart disease [adjusted odds ratio (aOR) 1.99; P = 0.03] and thrombosis (aOR 2.87; P = 0.01). In our analysis, HIV status was not significantly associated with either age at diagnosis of heart disease (median 53 years for HIV‐positive GBM versus 55 years for HIV‐negative GBM; P = 0.64) or 5‐year cardiovascular disease (CVD) risk estimated using the Framingham risk score. Conclusions: HIV‐positive GBM more commonly reported heart disease and thrombosis compared with their HIV‐negative peers. These results further highlight the need to understand the impact of HIV on age‐related comorbidities in GBM, to guide optimal screening and treatment strategies to reduce the risk of these comorbidities among the HIV‐positive population.